Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai (Studi Pada Pegawai Lembaga Dewan Kawasan Perdagangan Bebas Pelabuhan Bebas Batam Bintan Karimun) - Syazhashah Putra Bahrum; Inggrid Wahyuni Sinaga (Politeknik Negeri Batam, 2015)
This study aimed to examine the effect of leadership and motivation on employee performance either partially or simultaneously on Institutions Council of the Free Port Free Trade Zone of Batam Bintan Karimun. The research method used is descriptive research methods and statistics with a sample of 41 respondents. Data was collected using questionnaires and data analysis method used is multiple linear regression analysis.This research was conducted with a total population of 41 people. Retrieving data using the census, so that data is taken from the entire population. The variables in this study is divided into two, namely the independent and dependent variables. The independent variables consist of leadership and motivation, and the dependent variable is the performance of employees. This research was conducted by examining the validity and reliability of the instrument, then the data is analyzed and tested using Test F.The results showed that leadership, motivation and performance of staff of the Institute Council Free Port Free Trade Zone of Batam Bintan Karimun already can be quite high. Leadership and motivation high impact on employee performance improvement that is equal to 46% and the rest influenced by other factors not mentioned in this study.